DataSet. Datos BSSR en Primaria. - Merino-Marban, Rafael; Mayorga-Vega, Daniel; López-Fernández, Iván (Universidad de Málaga, 2025)
The purpose of this study was to research the effect of a stretching program on hamstring flexibility in schoolchildren from Primary Education. Methods. For practical reasons and the nature of the present study (i.e. intervention focused on natural groups in a school setting) a cluster-randomized controlled design was used. Balanced by school and grades, natural classes were assigned randomly to form one of the following study groups: warm-up group (WUG), cool-down group (CDG), mix group (MXG) and non-stretching group (NSG). A total of 222 children from Primary Education (117 girls and 105 boys; average age: 8.82 ±1.63 years; weight: 36.89 ±10.69 kg; height: 137.18 ±11.13 cm; BMI: 19.26 ±3.54) A total of 289 from Primary Education, average age: 9.5 years; weight: 37.1 ±10.8 Kg; height: 137.2 ±11.1 were divided into four groups (3 experimental groups and 1 control group). The 3 experimental groups performed hamstring stretches for 4 minutes during each Physical Education class over a two-month period, 2 sessions per week (8 weeks, for a total of 16 PE sessions), with a stretch duration of 20 seconds, utilizing the static passive technique. The EG1 performed the stretching exercises during warm-up (4 minutes), the EG2 performed the stretching exercises during cool-down (4 minutes) and finally the EG3 performed the stretching exercises during warm-up (2 minutes) and cool-down (2 minutes) period. The control group followed the standard class program of PE classes. Hamstring flexibility was measured using the BS-SR test before and after the program. The statistical significance level was set at p < 0.05. All statistical analyses were performed using SPSS version 25.0 for Windows (IBM® SPSS® Statistics). Conclusion. The CDG that performed stretching in the cool down period is the one that achieved significant improvements ccompared with the WUG, MXG, and NSG (p ≤ 0.01; d = 0.50-0.71).
Keywords: Músculos - Flexibilidad; Niños; Educación física para niños; Hamstring muscles extensibility; BS S-R; Back Saber Sit and Reach; Schoolchildren; Flexibility; Children; Intervention; Field test